PENGARUH KARAKTERISTIK PERUSAHAAN DAN FAKTOR LAINNYA TERHADAP MANAJEMEN - Michella Pungesdika; Riki Sanjaya (E-Jurnal Akuntansi TSM, 2022)
The objective of this research is to obtain empirical evidence about the effect of audit quality, board of independent commissioner, audit committee, firm size, financial leverage, firm age, return on assets, institutional ownership, and managerial ownership towards earnings management. Population of this research are non-financial firms listed in Indonesia Stock Exchange (IDX) from 2018-2020. Samples are selected using purposive sampling method and 312 data are used. Hypotheses in this research was analyzed using multiple linear regressions. The result of this research showed that audit quality and return on assets have effect on earnings management, whereas board of independent commissioner, audit committee, firm size, financial leverage, firm age, institutional ownership, and managerial ownership do not have effect on earnings management.